TINGKAT KEBUGARAN JASMANI SISWA PUTRA USIA 13-15 TAHUN DI SMP NEGERI 03 DOLOPO MADIUN - Brellians Syach, Muhammad Rifaldo; Nurhidayat, Nurhidayat (Jurnal Porkes, 2024)
The purpose of this study was to assess the nutritional status and physical fitness of male students aged 13-15 years. Quantitative descriptive research method with survey technique. The population is all male students aged 13-15 years. Sampling using purposive sampling technique 11 students. Data collection using tests and measurements. The instrument used the 2022 Indonesian student fitness test (TKPN) from the Ministry of Youth and Sports. The results of a total of 11 students who became research subjects. In undernutrition (thinness), 54% (6 students), good nutrition (normal) 36% (4 students), overnutrition (overwieght) 10% (1 student), obesity (obesity) 0% (0 students). In the sit up test, very low 100% (11 students), low 0% (0 students), sufficient 0% (0 students), good 0% (0 students), very good 0% (0 students). On squad thurst very low 0% (0 students), low 9% (1 student), fair 36% (4 students), good 18% (2 students), excellent 36% (4 students). In the pacer test very low 100% (11 students), low 0% (0 students), sufficient 0% (0 students), good 0% (0 students), excellent 0% (0 students). Then V Sit & Reach is very low 0% (0 students), low 0% (0 students), sufficient 45% (5 students), good 55% (6 students), excellent 0% (0 students). The conclusion is that most students aged 13-15 years have inadequate and unbalanced nutritional conditions. However, there are also some students who fall into the category of good (normal) nutrition with a total of 4 students.